Elimination and active extrusion of liver mitochondrial proteins during lipopolysaccharide administration in rat. Issue 5 (13th September 2012) - Unuma, Kana; Aki, Toshihiko; Matsuda, Seiji; Funakoshi, Takeshi; Yoshida, Ken‐ichi; Uemura, Koichi
Abstract : Aim: The purpose of the present study was to identify molecular markers of hepatic damage during lipopolysaccharide (LPS) treatment. Methods: LPS (15 mg/kg of bodyweight) or vehicle was injected i.p. into 5‐week‐old male Sprague–Dawley rats. Proteins were extracted from the liver and were electrophoresed to examine the changes in the protein compositions during LPS treatment. Using a proteomic approach, major LPS‐responsible protein in the liver was determined. Results: A massive reduction in the levels of carbamoyl phosphate synthase‐1 (CPS1), one of the most abundant proteins in liver mitochondria, was revealed during LPS administration. Electron microscopic and immunofluorescence analyses revealed large vacuoles, which were often localized in the vicinity of mitochondria, in the LPS‐treated rat liver. Furthermore, we found that CPS1 is released into the circulation prior to liver damage marker alanine aminotransferase, indicating the active extrusion of CPS1 during LPS administration. Another liver mitochondrial protein, ornithine transcarbamylase, is also released into the circulation, implicating active extrusion of mitochondrial proteins. These phenomena are accelerated by a heme oxygenase inducer cobalt protoporphyrin whilst suppressed by a lysosome inhibitor chloroquine. Conclusion: Plasma CPS1 should be a possible marker of septic liver damage and may be involved in systemic responses elicited by septic shock.